Pedagogia Libertadora e Pedagogia Histórico-Crítica: aproximações e distanciamentos - Roteski, Nayara (2021)
This work addresses two pedagogical trends led by Brazilian educators: the Liberating Pedagogy, by Paulo Freire, and the Historical-Critical Pedagogy, by Demerval Saviani. The main objective is to carry out a comparative study of those trends, seeking to identify their approximations and their distances in relation to, mainly, their theoretical-philosophical foundations. From a methodological viewpoint, the research has a bibliographic character, constituted from a bibliographical review. The main works consulted in this research are from the authorship of Freire (Educação como Prática da Liberdade e Pedagogia do Oprimido) and of Saviani (Escola e Democracia e Pedagogia Histórico-Crítica: Primeiras Aproximações), also the works from authors that analyze and/or develop new reflections from the contributions of the Liberating Pedagogy and Historical-Critical Pedagogy. As results from the research, it was found that the conception of man in each of the referred trends are according to the philosophical-theoretical references and experiences that the authors had contact throughout their trajectory, and in both, man differentiates himself from the animals by the process of labor, however, in the Liberating Pedagogy, this man receives a mystical connotation, with their vocation of being more, what is associated with Freire‟s link with Christianity. In relation to the school curriculums contents and to the importance of school, there are approximations and estrangements, as the criticism made by those authors about the trends that prevailed till then, especially, the Traditional Pedagogy. Both Freire and Saviani criticize this trend, however, while the former author denies it, the latter seeks to overcome it through incorporation.